Cuentos medievales: "La dama del castillo del gavilán" y el "Ejemplo de las flechas" Juan de Mandevilla, Libro de las maravillas del mundo - Rodríguez Temperley, María Mercedes (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2003)
Taking account of the last studies about medieval tales, which intend to enlarge the corpus of stories standing not only in tale collections but in very different texts, those included in Juan de Mandevilla's Libro de las maravillas del mundo are here tracked and classified. Likewise, it is performed the punctual analysis of two tales: "The lady of the sparrowhawk castle" and the "Exemplum of the arrows".